2012
DOI: 10.1002/btpr.1557
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Saccharomyces cerevisiae fermentation process for production of a therapeutic recombinant protein using a multivariate bayesian approach

Abstract: Various approaches have been applied to optimize biological product fermentation processes and define design space. In this article, we present a stepwise approach to optimize a Saccharomyces cerevisiae fermentation process through risk assessment analysis, statistical design of experiments (DoE), and multivariate Bayesian predictive approach. The critical process parameters (CPPs) were first identified through a risk assessment. The response surface for each attribute was modeled using the results from the Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In previous work, we reported the optimization of a S. cerevisiae high-cell density fed-batch process using a Bayesian approach [17]. The set points for critical process parameters (CPPs), temperature, pH and dissolved oxygen (DO), were selected based on the high probability region calculated to meet the acceptance criteria of relevant attributes for process performance and product quality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous work, we reported the optimization of a S. cerevisiae high-cell density fed-batch process using a Bayesian approach [17]. The set points for critical process parameters (CPPs), temperature, pH and dissolved oxygen (DO), were selected based on the high probability region calculated to meet the acceptance criteria of relevant attributes for process performance and product quality.…”
Section: Resultsmentioning
confidence: 99%
“…The product accumulation profiles were also consistent with a sustained increase of product concentration (measured as broth titer) up to the maximum of approximately 1.8 g/L by the EOR (Figure  1C). The quality attributes were also highly comparable between the batches (see Table four in [17]). The results indicated that the process had good controllability for each of the CPPs, and a consistent performance, and hence was ready for scale-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations